Semaphorin-6A controls guidance of corticospinal tract axons at multiple choice points. - MITCHELL, KEVIN; LITTLE, GRAHAM (My University, 2008)
Background: The trajectory of corticospinal tract (CST) axons from cortex to spinal cord involves a succession of choice points, each of which is controlled by multiple guidance molecules. To assess the involvement of transmembrane semaphorins and their plexin receptors in the guidance of CST axons, we have examined this tract in mutants of Semaphorin-6A (Sema6A), Plexin- A2 (PlxnA2) and Plexin-A4 (PlxnA4). Results: We describe defects in CST guidance in Sema6A mutants at choice points at the midhindbrain boundary (MHB) and in navigation through the pons that dramatically affect how many axons arrive to the hindbrain and spinal cord and result in hypoplasia of the CST. We also observe defects in guidance within the hindbrain where a proportion of axons aberrantly adopt a ventrolateral position and fail to decussate. This function in the hindbrain seems to be mediated by the known Sema6A receptor PlxnA4, which is expressed by CST axons. Guidance at the MHB, however, appears independent of this and of the other known receptor, PlxnA2, and may depend instead on Sema6A expression on CST axons themselves at embryonic stages. Conclusion: These data identify Sema6A as a major contributor to the guidance of CST axons at multiple choice points. They highlight the active control of guidance at the MHB and also implicate the inferior olive as an important structure in the guidance of CST axons within the hindbrain. They also suggest that Sema6A, which is strongly expressed by oligodendrocytes, may affect CST regeneration in adults.
PUBLISHED
Keywords: Genetics